TOPO mediated rapid hydrothermal synthesis and study of electrochemical performance of nano-structured copper oxide thin films. Issue 2 (3rd February 2017) - Teli, A. M.; Navathe, G. J.; Patil, D. S.; Jadhav, P. R.; Patil, S. B.; Dongale, T. D.; Karanjkar, M. M.; Shin, Jae Cheol; Patil, P. S.
Abstract : This paper reports the synthesis of trioctylphosphine oxide (TOPO) assisted copper oxide (CuO) electrodes by a rapid hydrothermal technique. Abstract : This paper reports the synthesis of trioctylphosphine oxide (TOPO) assisted copper oxide (CuO) electrodes by a rapid hydrothermal technique. The effects of the capping agent (TOPO) on structural, morphological and electrochemical properties for different concentrations of the Cu precursor were investigated. Surface morphology was examined by using scanning electron microscopy (SEM) which showed a yarn ball-like morphological structure for a lower concentration of the Cu precursor and rising of leaves onto the yarn balls was observed for higher concentrations. The cyclic voltammogram (CV) study showed the highest specific capacitance of about 143 F g −1 for CuOT3 at 10 mV s −1 and an energy density of 18.1 W h kg −1 at 1 mA cm −2 with about 82% capacitance retention after 1000 CV cycles at 100 mV s −1 in 1 M aq. KOH. Also the statistical model for capacitance retention and specific capacitance using the fitted exponential model was studied. Therefore, the specific capacitance can be tailored by appropriate selection of concentrations of the Cu precursor and TOPO.